Processing Coconut Fruit into Serundeng as an Effort to Utilize the Natural Potential of Ban Village, Karangasem - -, gek ayu sagita widya tresna wati; Sang Ayu Made Agung Prasetiawati Djelantik; Gusti Ngurah Oka Jiwantara (Gema Agro, 2024)
Ban Village, Kubu, Karangasem has an advantage in its natural potential, namely coconut trees. The natural potential in the form of coconut trees in Ban Village, Kubu, Karangasem has not been optimized to the fullest because the majority of people only utilize it by selling it in the form of coconut fruit, it has not been used as a superior food product that can increase the value of the economic potential of the village community. The purpose of this service is so that the community can utilize the natural potential in the village of Ban, Kubu, Karangasem so that it can have economic value with the hope that in the future this natural potential can be used as a superior food product that can increase the value of the economic potential of the Ban village community, Kubu, Karangasem. This service activity succeeded in attracting the attention of the government and the people of Ban Village, Kubu, Karangasem.